Atopic dermatitis. Interdisciplinary diagnostic and therapeutic recommendations of the Polish Dermatological Society, Polish Society of Allergology, Polish Pediatric Society and Polish Society of Family Medicine. Part II. Systemic treatment and new therapeutic methods - Nowicki, Roman; Trzeciak, Magdalena; Kaczmarski, Maciej; Wilkowska, Aleksandra; Czarnecka-Operacz, Magdalena; Kowalewski, Cezary; Rudnicka, Lidia; Kulus, Marek; Mastalerz-Migas, Agnieszka; Peregud-Pogorzelski, Jarosław; Sokołowska-Wojdyło, Małgorzata; Śpiewak, Radosław; et al. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
The treatment goal in atopic dermatitis is eliminating clinical symptoms of the disease, preventing exacerbations and complications, as well as improving patients’ quality of life. In cases of severe atopic dermatitis and lack of response it is recommended to introduce systemic therapy. Patients ofter require multi-specialist consultations, and occasionally hospitalization. It is not recommended to use acupuncture, acupressure, bioresonance, homeopathy, or Chinese herbs in the treatment of atopic dermatitis.